2014
DOI: 10.1097/scs.0000000000001058
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Split Osteotomy on the Previously Reconstructed Mandible With Fibula Free Flap

Abstract: The fibula free flap offers several advantages in mandibular reconstruction, including an optimal length and bone quality for dental implantation; therefore, the use of this flap has become a method of choice for mandibular reconstruction. Although the development of computer-assisted surgical planning has increased the accuracy of mandibular reconstruction, some unexpected outcomes still occur in clinical settings. The patient in this report underwent mandibular reconstruction with the fibula free flap becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…5 The asymmetric mandibular contour and the weak profile could be detrimental to the quality of life for patients with a secondary dentomaxillofacial deformity. Although some studies reported the use of sliding fibula osteotomy to treat malocclusion following mandibular reconstruction with the fibula free flap, [6][7][8] a second operation is needed, and the correction of the maxilla is likely to be neglected, thereby leading to a compromised treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…5 The asymmetric mandibular contour and the weak profile could be detrimental to the quality of life for patients with a secondary dentomaxillofacial deformity. Although some studies reported the use of sliding fibula osteotomy to treat malocclusion following mandibular reconstruction with the fibula free flap, [6][7][8] a second operation is needed, and the correction of the maxilla is likely to be neglected, thereby leading to a compromised treatment outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Large bone defects that arise from mandibular resection can be successfully managed by fibula free flap placement [11]. Currently, the minimization of surgical errors is directly related to improved aesthetic outcomes and functional recovery [12]. In our case, to reduce the likelihood of surgical error and to reduce the operation time, a virtual surgery simulation was performed based on the preoperative CT imaging, and a rapid prototype model was prepared based on the results of the simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Their technique introduced the use of stepped osteotomy in the fibular reconstructed mandible and showed that this method could correct for vertical or horizontal length defects. Kim et al [12] reported that sagittal split osteotomy of previously grafted fibula including the affected mandible ramus has several advantages. They found that the stepped osteotomy method can result in a significant interosseous gap and cause instability of the final occlusion for a long period after surgery, while the SSRO approach increased bone contact which maximized postoperative bone stability.…”
Section: Discussionmentioning
confidence: 99%
“…The realization of anteroposterior and lateral cephalometries, panoramic x-rays, standardized photographs, study models and three-dimensional reconstruction CT scan images is suggested. 2…”
Section: Discussionmentioning
confidence: 99%
“…Despite the use of these tools and guides that are able to minimize the margin of error as far as the length, position and direction of the bone segments during the reconstruction, a perfect outcome cannot always be guaranteed. 2 4…”
Section: Introductionmentioning
confidence: 99%